ChemInform Abstract: Solvothermal Syntheses, Crystal Structures, and Properties of Lanthanide(III) Thioarsenates [Ln(dien)2(μ‐1ϰ, 2ϰ2‐AsS4)] n (Ln: Sm, Eu, Gd) and [Ln(dien)2(1ϰ2‐AsS4)] (Ln: Tb, Dy, Ho). Issue 49 (3rd December 2013) - Wang, Fang; Tang, Chunying; Chen, Ruihong; Zhang, Yong; Jia, Dingxian
Abstract Solvothermal reactions of Ln2O3, As and S in diethylenetriamine (dien) (autoclave, 170 °C, 6 d) yields two structural types of lanthanide thioarsenates of general formulae [Ln(dien)2(μ‐1ϰ, 2ϰ2‐AsS4)] n (Ln: Sm, Eu, Gd) and [Ln(dien)2(1ϰ2‐AsS4)] (Ln: Tb, Dy, Ho) in 45—57% yield.